2015
DOI: 10.13189/ijrh.2015.030105
|View full text |Cite
|
Sign up to set email alerts
|

Devolution as a Means for Self-governance: Its Potential for Poverty Reduction in Kenya

Abstract: This study examined devolution which was introduced in Kenya at the beginning of 2013 with a view to establishing whether it was helping to reduce poverty as provided for in the Republic of Kenya Constitution (RoK, 2010). As is the case in other African countries, the majority of Kenyans are poor. We gathered data through desk reviews of relevant books, journal articles and reports and interviews with senior staff of Kakamega, Kisumu and Kajiado counties. It was evident that after abolishing Kenya's independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…In their earlier study, Chitere and Ngundo (2015) found, among other things, that the three counties of Kakamega, Kisumu and Kajiado were among Kenya's 47 counties. Whereas Kakamega and Kisumu counties are in western Kenya with their indigenous inhabitants being Luhya and Luo, respectively while Kajiado to the southern part of the country is a semi-arid pastoralist whose indigenous inhabitants are Masaai.…”
Section: The Counties and Their Governance Systemsmentioning
confidence: 96%
See 4 more Smart Citations
“…In their earlier study, Chitere and Ngundo (2015) found, among other things, that the three counties of Kakamega, Kisumu and Kajiado were among Kenya's 47 counties. Whereas Kakamega and Kisumu counties are in western Kenya with their indigenous inhabitants being Luhya and Luo, respectively while Kajiado to the southern part of the country is a semi-arid pastoralist whose indigenous inhabitants are Masaai.…”
Section: The Counties and Their Governance Systemsmentioning
confidence: 96%
“…In their earlier study, Chitere and Ngundo (2015) found that the three counties were poor when examined on the basis of indicators such as high population density, especially in Kakamega and Kisumu, low literacy rate, teacher: pupil ratio and infant and child mortality. This poverty situation was examined further by asking respondents about the needs/problems of their towns.…”
Section: Poverty Situation Of the Counties And The Individual Respondmentioning
confidence: 98%
See 3 more Smart Citations